2017
DOI: 10.7595/management.fon.2017.0022
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of advertising media on brand awareness

Abstract: In modern business conditions, the company sends its promotional message through various instruments of promotion, and therefore the different media. One of the instruments of promotion is economic propaganda (advertising), which uses a number of media such as television, radio, newspapers, billboards, Internet and others. By using various media, the company affects the consumer awareness of the brand, spreads information about themselves and the brand, educates consumers, creates a brand image and the like. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
18
0
4
Order By: Relevance
“…The widespread popularity of the web and the internet has led to an intense growth of commercial product publicity online via advertisements and also it is said that the visual advertisements portrayed on television and social media are a crucial medium of attracting customers towards a product (Vedula et al, 2017). As emphasized by previous studies, advertisements provide information about products and services to individuals (Domazet et al, 2017;Terui et al, 2011). While discussing the previous literature, it can be understood that quality and the meaning of the content in an advertisement is an important influencing factor in social media marketing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread popularity of the web and the internet has led to an intense growth of commercial product publicity online via advertisements and also it is said that the visual advertisements portrayed on television and social media are a crucial medium of attracting customers towards a product (Vedula et al, 2017). As emphasized by previous studies, advertisements provide information about products and services to individuals (Domazet et al, 2017;Terui et al, 2011). While discussing the previous literature, it can be understood that quality and the meaning of the content in an advertisement is an important influencing factor in social media marketing.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents reported that creativity and the distinctiveness in the content of the advertisement exhibit itself as a form of entertainment, and the participants of the current study had reported that they tend to watch such advertisement again. Previous studies have also emphasized the importance of original, creative, and different advertisements and advertising strategies to improve positive perceptions towards the products or services (Buil et al, 2013;Domazet et al, 2017). Creativity has been proven as a cornerstone for the development of effective advertisements (Sasser & Koslow, 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Humor in ads is categorized as an emotional appeal (El Tazy and Dinana, 2018). Humor can be explained as a very effective device in the media, specifically in TV advertisements (Domazet et al, 2017). Humorous advertising is a psychological response considered by the positive emotion of entertainment, the evaluation that something is funny, and makes the audience laugh (Eisend, 2017).…”
Section: Literature Review: 21 Humorous Advertisingmentioning
confidence: 99%
“…Also, brand awareness has two aspects brand depth and width, depth recommend how to make customer recall a brand and width express the result when the brand name come to the customers' mind during the purchasing situation (Keller, 2013) Brand awareness is created through advertising like TVC, Radio, Social media etc. (Khan, Jadoon and Tareen, 2016), as the study of (Domazet, Đokić and Milovanov, 2017) pointed out that it should be present for about two-thirds of the time, moreover the context of advertising influence on brand awareness is in some researches associated to consumers' or situational characteristics. Humorous advertising has become a famous and regularly used when interacting with the company's target customers, which helps in the formation of awareness and attention, and in improving attitudes towards the brands according to (Senthilkumar, and Venkatesh, 2017).…”
Section: Brand Awarenessmentioning
confidence: 99%
“…"Internet marketing may be defined as using the Internet as a virtual store where products are being sold directly to consumers", (Corley, Jourdan & Ingram, 2013, p. 177). The research carried out by Domazet, Djokic & Milovanov (2017) showed that the Internet has a big influence on consumers (on brand awareness) in Serbia, immediately after the influence of television.…”
Section: Internet Marketing As a Form Of Direct Marketingmentioning
confidence: 99%